Respostas

2014-04-15T17:04:25-03:00


Vamos calcular

f(5) => f(5) = 5 - 3 * 5 = 5 - 15 = -10

f(1) => f(1) = 5 - 3 * 1 = 5 - 3 = 2

g(3) => g(3) = 7 * 3 - 8 = 21 - 8 = 14

g(8) => g(8) = 7 * 8 - 8 = 56 - 8 = 48


f(5) + g(3) = -10 + 14 = 4

f(1) + g(8) = 2 + 48 = 50

 Assim temos: 4 / 50 = 2 / 25


Bons estudos.

De um melhor resposta ae. vlw
Você confundiu em um pequeno detalhe. É f(1) vezes g(8), e não f(1) + g(8). Ai ficaria 2.48 = 96
2014-04-15T17:13:35-03:00
  f(5) + g(3)   
  f(1) . g (8) 

f(5) = 5 - 3.5 = 5 -15 = -10
g(3) = 7.3 - 8= 21-8 = 13 
f (1) = 
5 - 3.1 = 5-3 = 2 
g(8) =  7.8 - 8 = 56-8 = 48 

-10 +13  =   3   =    1  
 2  .48       96        32
2 4 2